Extent of the Legality of the Use of Drones in International Humanitarian Law - المالكي هادي نعيم; جعفر محمود خليل (Journal of Legal Sciences, 2019)
Rules of international humanitarian law establish restrictions on parties to armed conflicts in the their choice of weapons, means and methods of warfare. States when develop or acquire new weapons should verify that it complies with these rules. Current progress by new technology indicates that is very important to continue to assess the legality of new weapons.